Constructing a Diagnostic Scale to Distinguish between Surface and Deep Dyslexia in the Light of the Dual-route Model for Reading and Detecting its Effectiveness in the Jordanian Environment - Mayada Al-Natour; Faten Al-Mashayek (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims at constructing a diagnostic scale to distinguish between surface and deep dyslexia in the light of the dual-route model, verifying its psychometric characteristics and detecting the differences in its lexical route and non-lexical route according to the reading routes mentioned in the dual-route model of reading. The study sample of 120 students, was chosen from the fourth grade in public and private schools in the directorates of education in Al-Mazar and Al-Karak. The scale consisted of (230) items distributed to three domains: non-lexical route, lexical route, and diagnosing the characteristics of deep dyslexia. The results verified the instrument's validity and reliability. The results revealed that there are statistically significant differences at (α=0.05) between the mean scores for the performance of the surface and deep-dyslexic students and the non-dyslexic students in favor of the non-dyslexic students. The results showed that the performance of surface-dyslexia students was better in the non-lexical route and the characteristics of deep dyslexia, while their performance was lower in the lexical route, indicating the healthy case of the non-lexical route and the unhealthy case of the lexical route among the students with surface dyslexia. The deep-dyslexic students had lower scores on all the domains of the scale, indicating the unhealthy state of both lexical and non-lexical routes; therefore, the characteristics of deep dyslexia apply to them. This indicates that the scale, he thought of as the dual-route model for reading, is capable of distinguishing between two sub-types of dyslexia: surface dyslexia and deep dyslexia.